Brass metallurgy in Urartu: Recent evidence from eastern Anatolia - Guder, Umit; Ozdemir, Abdulkadir; Vercik, Marek (Elsevier, 2023)
Traditionally, the beginning of substantial and deliberate brass production through the cementation process has been placed to the Early Roman period. Sporadic early finds have accordingly been considered to be the result of various experimentations by eastern Mediterranean metallurgists at least since the Late Bronze Age. Several Anatolian finds, dated to the early first millennium BC, that were made from zinc rich alloys have been inter-preted within this framework. In ancient Urartu, however, the mastery and application of advanced metal technologies of both casting and working of copper-alloys as well as blacksmithing are well documented. This study aims to provide a further understanding of this phenomenon by shedding light on the development of zinc metallurgy in eastern Anatolia based on recent finds unearthed during the rescue excavations at Murat Tepe and Murat Ho center dot yuk in the Murat River basin in modern eastern Turkiye. In both cases the metal assemblages from stratified contexts were analysed by the means of multiple archaeometallurgical methods. The results from portable XRF (pXRF), metallography, micro-hardness, scanning electron microscopy-energy dispersive X-ray spectrometry (SEM-EDS) and Raman spectroscopy analyses have showed that zinc was intentionally used as an alloy additive in order to fabricate brass. Moreover, in one case, the chemical composition consisting of zinc (Zn), tin (Sn) and copper (Cu) was detected, which indicates different alloying practices for the production of different types of objects. These new observations raise further questions about the deliberate production and manufacturing of brass prior to the wide spread of this metal technology in the Roman period.
Keywords: Brass; Zinc; Urartu; Anatolia; Archaeometallurgy